2014
DOI: 10.2478/ace-2014-0002
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Safety Performance Function for Urban Unsignalized Four-Legged One-Way Intersections in Palermo, Italy

Abstract: Starting from consideration that urban intersections are sites with promise for safety and operational improvements, the paper describes the steps taken to develop a crash predictive model for estimating the safety performance of urban unsignalized intersections located in Palermo, Italy. The focus is on unsignalized four-legged one-way intersections widespread in Italian downtowns. The sample considered in the study consist of 92 intersections in Palermo, Italy. For the study were collected crashes occurred i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Moreover, Donnell et al (2016) used 50 intersections with 100 crashes per year in total to develop SPFs in their study. A study from Italy reported that researchers used 7 years of crash data consisting of 644 crashes that occurred at 92 unsignalized urban intersections (Giuffrè et al 2014). In some cases, due to data limitations, researchers also combined crashes that have different severities, such as fatality and incapacitating injuries, in order to obtain a reasonable data set size (Savolainen et al 2015).…”
Section: Data Requirements For Spfs and Cmfsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Donnell et al (2016) used 50 intersections with 100 crashes per year in total to develop SPFs in their study. A study from Italy reported that researchers used 7 years of crash data consisting of 644 crashes that occurred at 92 unsignalized urban intersections (Giuffrè et al 2014). In some cases, due to data limitations, researchers also combined crashes that have different severities, such as fatality and incapacitating injuries, in order to obtain a reasonable data set size (Savolainen et al 2015).…”
Section: Data Requirements For Spfs and Cmfsmentioning
confidence: 99%
“…In addition, Giuffrè et al (2014) reported that minor and major approach AADTs along with number of lanes were the best variables that should be used when developing SPFs for intersections. Vogt (1999), on the other hand, employed traffic and geometric variables to establish crash models.…”
Section: Crash Models and Safety Performance Functionsmentioning
confidence: 99%
“…Several parameterizations of the NB models are available in the literature. Nonetheless, the NB-1 and NB-2 (Cameron and Trivedi, 1986) have been commonly used to model the count data (Wang et al, 2019;Giuffrè et al, 2014;Ismail and Zamani, 2013;Hilbe, 2011;Winkelmann, 2008;Chang and Xiang, 2003;Miaou and Lord, 2003). The two models necessarily differentiate on the basis of the relationship between the variance of the data and the mean of the data.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that both models showed consistent results for the relationship between crashes and traffic volume, the number of through lanes, and median. Giuffrè et al (2014) applied the NB-1 and NB-2 models to develop the SPFs for urban unsignalized intersections. They found that the NB-1 fits the data better than the NB-2.…”
Section: Introductionmentioning
confidence: 99%
“…International studies (Sacchi et al 2012;Cafiso et al 2012;Cunto et al 2015;Persaud and Nguyen 1998;Giuffre et al 2014;Martinelli et al 2009) also show that sampling of sites is often hindered by the availability of data. Studies in Brazil (Cunto et al 2015) and Italy (Giuffre et al 2014;Martinelli et al 2009) found the need for manually collected data on traffic volumes, roadway geometry, and functional characteristics limited the number of sites that could feasibly be included in SPF estimation.…”
Section: Summary Of State Efforts In Spf Calibration and Developmentmentioning
confidence: 99%